The phytomicrobiome: solving plant stress tolerance under climate change - Khan, Abdul Latif (Frontiers in Plant Science, 2023)
With extraordinary global climate changes, increased episodes of extreme conditions result in continuous but complex interaction of environmental variables with plant life. Exploring natural phytomicrobiome species can provide a crucial resource of beneficial microbes that can improve plant growth and productivity through nutrient uptake, secondary metabolite production, and resistance against pathogenicity and abiotic stresses. The phytomicrobiome composition, diversity, and function strongly depend on the plant's genotype and climatic conditions. Currently, most studies have focused on elucidating microbial community abundance and diversity in the phytomicrobiome, covering bacterial communities. However, least is known about understanding the holistic phytomicrobiome composition and how they interact and function in stress conditions. This review identifies several gaps and essential questions that could enhance understanding of the complex interaction of microbiome, plant, and climate change. Utilizing eco-friendly approaches of naturally occurring synthetic microbial communities that enhance plant stress tolerance and leave fewer carbon-foot prints has been emphasized. However, understanding the mechanisms involved in stress signaling and responses by phytomicrobiome species under spatial and temporal climate changes is extremely important. Furthermore, the bacterial and fungal biome have been studied extensively, but the holistic interactome with archaea, viruses, oomycetes, protozoa, algae, and nematodes has seldom been studied. The inter-kingdom diversity, function, and potential role in improving environmental stress responses of plants are considerably important. In addition, much remains to be understood across organismal and ecosystem-level responses under dynamic and complex climate change conditions.